Pengaruh Campuran Media Tanam Pelepah Kelapa Sawit Terhadap Hasil Jamur Tiram Putih (Pleurotus ostreatus) - abdurahman, chamim; Drs. Inpurwanto, M.Si, Drs. Inpurwanto, M.Si; Ahmad Mulyai, S.Si, M.Si, Ahmad Mulyai, S.Si, M.Si (Jurnal Sains Pertanian Equator, 2016)
The white oyster mushroom (Pleurotus ostreatus) is the plant that widely cultivated. This plant has a harvesting period that is fast enough and has a variety of health benefits. Planting media which is used in this research is a mixture of dry and wet of the stem of palm oil powder. This research aims to determine the effect of the mixture of dry and wet of the stem of palm oil powder on the jamur tiram crop yields and to determine the best planting media mixture on the white oyster mushroom crop yields. The research uses a completely randomized design with one factor which consists of 7 treatments, namely: p0 (control / with sawdust), p1 (100% the stem of palm oil dry powder), p2 (80% the stem of palm oil dry powder + 20% the stem of palm oil wet powder), p3 (60% the stem of palm oil dry powder + 40% the stem of palm oil wet powder), p4 (40% the stem of palm oil dry powder + 60% the stem of palm oil wet powder), p5 (20% the stem of palm oil dry powder + 80% the stem of palm oil wet powder), and p6 ( 100% the stem of palm oil wet powder). Each treatment consists of 4 times planting experiment and each planting experiment consists of two samples. The research is conducted in Jl. Parit Baru Rintis, Punggur Kecil Village, Sungai Kakap Subdistrict, Kubu Raya Regency, and West Borneo Province. The results showed significant effect on the variable amount of fruit weight and average production of oyster mushroom, while the other variables showed no real effect. The conclusion of this study is powder palm fronds can be used as a medium for the cultivation of oyster mushroom. Treatment of growing media by using 40% + 60% the stem of palm oil wet powder of the dry powder is the most effective midrib on crop yields oyster mushroom.